Impact of Metabolisable Protein and Energy Levels in the Rations on Performance of Male Buffalo Calves - Niranjan, S. K.; Thakur, Manjula; Bhakat, M.; Tyagi, N.; Mohini, Madhu (Indian Journal of Animal Nutrition, 2017)
This study was conducted to determine the effect of different levels of metabolizable protein (MP) and metabolizable energy (ME) on nutrients utilization, nitrogen metabolism, blood biochemical profile and growth performance in Murrah buffalo calves. Sixteen growing male buffalo calves of similar body weight (222 kg) were divided into 4 groups of 4 animals each. The animals were offered four different total mixed rations containing different ME and MP levels viz., 100: 100; 115: 100; 100: 115; 115: 115% as per ICAR (2013) in groups T1, T2, T3 and T4, respectively. The animals were fed individually for 105 days. Dry matter intake was similar in all the treatments. The MP intake was similar in groups T3 and T4 but higher (P0.05) similar in groups T1 and T3 but lower than groups T2 and T4. The digestibility of nutrients (DM, OM and NDF) was higher (P